2019
DOI: 10.15421/011933
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Cameraria ohridella (Lepidoptera, Gracillariidae) on the activity of the enzymatic antioxidant system of protection of the assimilating organs of Aesculus hippocastanum in an urbogenic environment

Abstract: In the last two decades, the horse chestnut (Aesculus hippocastanum L.), introduced into the steppe zone of Ukraine, has been severely affected by the horse chestnut leaf miner Camereraria ohridella Deschka & Dimič, 1986, which results in damage to the assimilating organs, premature leaf defoliation and, as a consequence, a significant reduction in the reserve substances required for normal life of the plant. In recent studies, the main focus has been placed on the study of the pest’s effects on the non-en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 36 publications
2
9
0
6
Order By: Relevance
“…In the leaves of horse chestnut trees with a high level of damage by miners, expression of BPOD isoforms is activated in the pH range of 4.08-4.15. So, in August, and also as it was found in the work (Shupranova et al, 2019), the expression of the most acidic isoperoxidases significantly increases in plants unresistant to C. ohridella. At the same time, an increase in the degree of phytophage invasion practically does not change the activity of isoperoxidase 4.21, while the molecular forms of the enzyme with рІ 4.25, 4.42 and 4.58 respond with a decrease in activity compared to plants relatively resistant to Ae.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…In the leaves of horse chestnut trees with a high level of damage by miners, expression of BPOD isoforms is activated in the pH range of 4.08-4.15. So, in August, and also as it was found in the work (Shupranova et al, 2019), the expression of the most acidic isoperoxidases significantly increases in plants unresistant to C. ohridella. At the same time, an increase in the degree of phytophage invasion practically does not change the activity of isoperoxidase 4.21, while the molecular forms of the enzyme with рІ 4.25, 4.42 and 4.58 respond with a decrease in activity compared to plants relatively resistant to Ae.…”
Section: Discussionsupporting
confidence: 74%
“…Peroxidases are induced in many plants in response to insect attack and are an important component of the direct response to plant damage, as they regulate a number of processes directly or indirectly related to plant resistance to insect pests (War et al, 2018). Our previous study (Shupranova et al, 2019) carried out in July 2018 found an increase in the activity of benzidine peroxidase due to HCLM effect by an average of 46.0%. Our results showed that the activity of peroxidase in the leaves of horse chestnut plants in August from the same experimental sites but with a higher level of damage (78.3% and 97.5%) is significantly higher (2.2 and 2.1 times, respectively) than in the leaves of relatively resistant trees with damage level 13.3%.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Отримано результати (Seliutina et al, 2020), що демонструють активізацію ферментативної антиоксидантної системи захисту A. hippocastanum на пошкоджуючу дію каштанової мінуючої молі, що дозволяє рослині вижити і завершити програму онтогенезу в несприятливих умовах. Найбільш вагомим для захисту клітин від мінера є підвищення активності гваякол-пероксидази, що свідчить про посилення бар'єрних властивостей клітин (Shupranova et al, 2019).…”
unclassified